Thermal stability of nanocrystalline materials: thermodynamics and kinetics. (18th August 2017) - Peng, H. R.; Gong, M. M.; Chen, Y. Z.; Liu, F.
ABSTRACT: As nanocrystalline (NC) materials exhibit many unique properties, which are often superior to the properties of their coarse-grained counterparts, they offer significant potential for use in a variety of applications. Owing to their high volume fraction of grain boundaries, however, the intrinsic problem of poor thermal stability substantially limits the potential application of these materials. To solve this problem, thermal stability has become an important issue in the field of NC materials. This paper reviews the progress in the investigation of the thermal stability of NC materials with emphasis on the fundamentals of grain size stabilization by different approaches. First, the stabilizing approaches are classified into two categories, namely, thermodynamic stabilization and kinetic stabilization. Second, within the framework of thermodynamics and kinetics, the progress in theoretical models, experiments, and computer simulations is comprehensively reviewed. Third, strategies that are proposed to stabilise the grain size are summarised and discussed. This paper shows that the stabilization of NC materials is feasible and can be tailored by the selection of suitable strategies to satisfy the demands of different practical applications. Finally, several issues that require further investigation are identified.